Polyspermy Block in the Central Cell During Double Fertilization of Arabidopsis thaliana - Nagahara, Shiori; Takeuchi, Hidenori; Higashiyama, Tetsuya (Frontiers in Plant Science, 2021)
During double fertilization in angiosperms, two male gametes (sperm cells), are released from a pollen tube into the receptive region between two female gametes; the egg cell and the central cell of the ovule. The sperm cells fertilize the egg cell and the central cell in a one-to-one manner to yield a zygote and an endosperm, respectively. The one-to-one distribution of the sperm cells to the two female gametes is strictly regulated, possibly via communication among the four gametes. Polyspermy block is the mechanism by which fertilized female gametes prevent fertilization by a secondary sperm cell, and has been suggested to operate in the egg cell rather than the central cell. However, whether the central cell also has the ability to avoid polyspermy during double fertilization remains unclear. Here, we assessed the one-to-one fertilization mechanism of the central cell by laser irradiation of the female gametes and live cell imaging of the fertilization process in Arabidopsis thaliana. We successfully disrupted an egg cell within the ovules by irradiation using a femtosecond pulse laser. In the egg-disrupted ovules, the central cell predominantly showed single fertilization by one sperm cell, suggesting that neither the egg cell nor its fusion with one sperm cell is necessary for one-to-one fertilization (i.e., monospermy) of the central cell. In addition, using tetraspore mutants possessing multiple sperm cell pairs in one pollen, we demonstrated that normal double fertilization was observed even when excess sperm cells were released into the receptive region between the female gametes. In ovules accepting four sperm cells, the egg cell never fused with more than one sperm cell, whereas half of the central cells fused with more than one sperm cell (i.e., polyspermy) even 1 h later. Our results suggest that the central cell can block polyspermy during double fertilization, although the central cell is more permissive to polyspermy than the egg cell. The potential contribution of polyspermy block by the central cell is discussed in terms of how it is involved in the one-to-one distribution of the sperm cells to two distinct female gametes.